A Comparative Study of Biology Curricula in England, Scotland and the Czech Republic - Holec, Jakub (Scientia in educatione, 2019)
In recent years, both in the Czech Republic and abroad, there has been a debate about the renaissance of educational content and its intended form expressed in national curricula. From the curriculum analyses point of view, it is highly interesting to compare similar curricula created in different contexts, on the one hand, and different curricula created in similar contexts on the other hand. On the basis of the context-curriculum analysis, the curricula of England, Scotland and the Czech Republic were selected. The paper seeks to explore biology education in three National Curriculum Frameworks in the field of primary and lower secondary education. The comparative analysis is a tool for a deeper understanding the intended learning objectives as stated in the curricula. It provides an opportunity to compare different types of curricula and analyse biology content organization and the cognitive demands of the respective disciplinary knowledge, at least judging from the curriculum documents. The paper contributes to comparative curriculum research and provides the knowledge needed for the future process of curriculum review in the Czech Republic. I conclude that, while all these curricula emphasize learning outcomes and experiences, there are distinct differences between them in a stronger emphasis on the disciplinary knowledge or developing transversal competencies. It is reflected in both the learning outcomes formulation and the level of their specificity. This paper offers a contribution to the debate about the way in which particular disciplinary content is organized and taught from the perspective of a specific curriculum policy.